Malaria and soil-transmitted intestinal helminth co-infection and its effect on anemia: a meta-analysis - Cho Naing; Maxine Whittaker; Victor Nyunt-Wai; Simon Reid; Shew Fung Wong; Joon Wah Mak; Marcel Tanner (2013)
This study aimed to synthesize available evidence on the extent of malaria and soil-transmitted intestinal helminth (STH) co-infections in people living in endemic countries and to explore the effect of interactions between malaria and STHs on anemia. We searched relevant studies in electronic databases up to March 2013. Studies comparing malaria and STH co-infected patients with those not co-infected were included and the effect estimates were pooled using a random-effects model. We identified 30 studies for meta-analyses of which 17 were cross-sectional design. The majority of included studies (80%) were carried out in African countries. Among pregnant women, those infected with hookworm were found to have higher association with malaria infection compared with those without (summary OR: 1.36; 95% CI: 1.17–1.59; I2: 0%). Among non-pregnant adults, the summary OR of the association between anemia and the combined malaria and STH was 2.91 (1.38–6.14). The summary OR of the association between anemia and malaria alone was 1.53 (0.97–2.42), while the association between anemia and STH alone was 0.28 (0.04–1.95). There is no good evidence to support a different effect of malaria and STH on anemia. A subgroup analysis showed a higher risk of malaria infection in the primigravidae (summary OR: 1.61; 95% CI: 1.3–1.99; I2: 0%). In conclusion, the malaria–STH co-infection was variable with complex outcomes on anemia.